Criminality at work - Bogg, Alan; Collins, Jennifer, 1986-; Freedland, M. R. (Mark Robert); Herring, Jonathan (Oxford : Oxford University Press, 2020)
Edited by four leading law scholars, this volume explores the political and regulatory dimensions of modern 'criminality at work' from a wide range of disciplinary perspectives.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 30, 2020).
Keywords: Labor laws and legislation; Criminal law; Law; Laws of specific jurisdictions & specific areas of law